Challenges in diagnosing Treatment-Resistant Schizophrenia (TRS) with Frontal Lobe Atrophy from MRI Imaging: Case Study - Mardhiyah Rusdi; Faiz Md Tahir; Ahmad Zafri Abu Bakar; Hashlina Rusdi; Mohamad Rusop Mahmood; Roshidah Rusdi (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2022)
The diagnostic criteria for the behavioral variant of frontotemporal dementia were revised recently. Distinguishing both disorders apart as brain imaging studies in patients with schizophrenia also demonstrate changes in the frontal and temporal lobes which can help in the diagnostic process. This paper highlights the challenges in diagnosing Treatment-Resistant Schizophrenia (TRS) with a differential diagnosis of Fronto-Temporal Dementia (FTD) from magnetic resonance imaging (MRI) imaging. From the diagnosis of the case study, it can be summarized that frontotemporal atrophy is often associated with FTD but it may also occur in a patient suffering from schizophrenia. This provides a challenge for medical practitioners to distinguish between FTD and schizophrenia as disinhibition and executive dysfunction may prominent in schizophrenia with (Frontotemporal Atrophy) FTA.